Zoonoses and their traces in ancient genomes – a possible indicator for ancient life-style changes? - Leciej, Dawid; Herzig, Karl-Heinz; Thalmann, Olaf (Journal of Medical Science, 2020)
Humans are constantly exposed to health risks inherent to the environment in which they live, thereby including non-human fauna. Zoonoses are infectious diseases caused by agents such as bacteria, parasites, or viruses being transmitted to humans from wild animals and livestock. The close proximity of animals and humans facilitate the spread of zoonoses, so it is intriguing to hypothesize that populations accustomed to different lifestyles will also vary in the prevalence of zoonotic agents. The Neolithic era in human history is characterised by a dramatic transition in lifestyle, from hunting and gathering to farming. Thus, with the changes in the reservoir of animal species humans were exposed to zoonotic agents potentially penetrating human populations. Due to the rapid development of sequencing technologies and methodology in ancient DNA research, it is now possible to generate complete genomes of ancient specimens and pinpoint those genomic regions or epigenetic signatures that might be influenced by past zoonotic transmissions. Unravelling such traces, particularly on a population-scale, will help to overcome the lack of generalisation that hampered previous research focusing exclusively on the model fossils in human evolution, and facilitate a better understanding of the aetiology of diseases, including those caused by zoonotic agents.
Keywords: zoonoses; paleoepidemiology; paleogenomics; paleoepigenomics; neolithic; ancient DNA